Animal biobanks in Costa Rica: Governance, access to genetic resources, and challenges for biolaw - Valverde-Abarca, Anthony (2025)
Introduction. The concept of a biobank encompasses organized collections of biological material (tissues, fluids, cells, and DNA) and associated data for research purposes in both humans and animals. In Costa Rica, the development of ex situ collections within universities and public and private institutions contrasts with existing regulatory and operational gaps related to governance, custodianship, exchange of biomaterials and data, and the fair distribution of benefits. Objective. This study aims to analyze the ethical and legal principles and challenges associated with animal biobanks within the framework of biolaw. Methodology. A review of recent literature was conducted using the Scopus and Web of Science databases to determine the current state of the art in animal biobanks and the legislation governing them. Analysis. The development of biobanks has been driven by advances in the omics sciences and the emergence of large electronic databases. However, significant challenges persist, including limited digital infrastructure, the absence of clear data management policies, and the reluctance of some researchers to share information. These obstacles vary across scientific disciplines and disproportionately affect early-career researchers. The principles of communality and disinterestedness underpin the ethical obligation to promote data sharing, yet they often conflict with considerations of intellectual property and scientific competitiveness. In the context of animal biobanks, their potential applications include biomedical research on human diseases, genetic and reproductive improvement, and the management of zoonotic disease outbreaks. Nevertheless, robust ethical and legal approaches and clear governance frameworks are required to maximize their utility. Conclusion. Although conventions, universal declarations, and international treaties exist, Costa Rica lacks specific regulations governing animal biobanks. Therefore, dedicated legislation in this area is necessary, particularly given the existence of established animal biobanks at the national level.